Influence of Green Accounting, Sales Growth, and Firm Size on the Quality of Capital Structure - Effendi, Bahtiar (Owner : Riset dan Jurnal Akuntansi, 2024)
Profit is the most important measurement tool for a company's success. The sustainability of a company is not determined solely by profits, but sustainability factors must be taken into account when carrying out the company's operational activities. The aim of this research is to find out whether green accounting, sales growth and company size have an influence on the company's capital structure. In addition, this research aims to analyze green accounting, sales growth and company size, which simultaneously have an impact on the company's capital structure. The companies examined in this study are manufacturing companies listed on the Indonesian Stock Exchange during 2019-2022. This research is quantitative research and the survey method is purposive sampling. The data analysis techniques used are multiple linear regression, coefficient of determination and hypothesis testing. The research results found that green accounting and sales growth had no impact on capital structure, company size had a significant impact on capital structure, and green accounting, sales growth and company size had a significant impact on capital structure at the same time. This research has provided a solid foundation for signaling theory as a basis for analyzes explaining how green accounting, earnings growth and firm size influence capital structure. It is hoped that these results can serve as a guide for preparing further research by adding more variables such as profitability as an intervening variable to improve the company's capital structure.